Obstacles of Incomplete Laboratory Documents Supporting Airworthiness Requirements for Hajj Pilgrims with a History of Anemia at the Surabaya Embarcation Hajj Dormitory: Case Report - Sumatika, Ainul Fardiah; Griana, Tias Pramesti (Proceeding Annual Symposium on Hajj and Umrah Medicine, 2025)
Background: This study addresses the challenge of incomplete laboratory documents hindering the flight eligibility assessment of hajj pilgrims with a history of anemia at the Surabaya Hajj Dormitory. Anemia, characterized by a decrease in hemoglobin levels or red blood cell counts, increases the risk of serious health complications during long-haul flights due to reduced oxygen-carrying capacity and hypoxia under cabin pressure conditions. Objective: The research objectives included evaluating the availability and completeness of recent blood laboratory tests essential for determining fitness to fly and highlighting the clinical implications of anemia in this context. Methods: Using a case report methodology, the study illustrated a typical scenario where incomplete laboratory documentation delayed proper medical evaluation and potentially endangered the pilgrim’s health during and after the flight. Findings underscore the critical role of comprehensive pre-flight hematological screening and consistent medical follow-up to ensure safe pilgrimage travel for individuals with anemia. Results: The study concludes that enhanced education, stringent document verification systems, and proactive healthcare management are imperative to minimize risks and support the safe participation of anemic pilgrims in the hajj pilgrimage. Species mentioned in hematological and clinical context are appropriately italicized to conform to scientific standards. Conclusion: This work contributes to improving health service protocols for hajj pilgrims, particularly those with preexisting anemia conditions, enhancing overall safety and compliance with international health regulations